Synthesis, crystal growth, physicochemical study of 1,3-dihexyl-2-me-thyl-1H-benzo[d]imidazol-3-ium bromide and in silico nonlinear optical property determination - Siddiqui, Zahir Ali; Gamidi, Rama Krishna; Sekar, Nagaiyan; More, Sandeep (Journal of Molecular Structure, 2024)
This study encompasses the synthesis and characterization of 1,3-dihexyl-2-methyl-1H-benzo[d]imidazol-3-ium bromide (DHBIB) using techniques such as NMR, IR, and HRMS. The study also explores the influence of different solvents, specifically water and acetonitrile, on the growth of single crystals. An intriguing observation is the transformation of crystal packing from orthorhombic to monoclinic when solvent conditions change, illustrating the pivotal role of the cation in controlling the crystal structure of DHBIB salts. The analysis of its electronic properties reveal a deep -lying LUMO (-3.73 eV), suggesting DHBIB's electron -accepting characteristics. Furthermore, the study records absorption maxima ( lambda max ) at 279 nm and 282 nm in various solvents, demonstrating that DHBIB lacks absorption in the visible range (400-800 nm), making it promising for non-linear optical (NLO) applications. Analysis of the natural bond orbital (NBO) stabilization energies 50.87, 42.12, and 45.33 kcal/mol along pi(C3-C4) -> pi*(C6-C8), pi(C3-C4) -> pi*(C10-C12), and pi (C10-C12) -> pi*(C6-C8) reveal a preference for intramolecular charge transfer in DHBIB. Enhanced first and second -order hyperpolarizabilities ( beta ; 13.47x10 -30 esu, gamma ; 75.36x10 - 36 esu) compared to benzimidazole and benzimidazolium salicylate salt further supports its potential for NLO applications.
Keywords: DHBIB; Hyperpolarizability; Monoclinic; NBO; Orthorhombic